Applicability of Metals as Liner Materials for Ammonoacidic Crystal Growth. Issue 11 (8th October 2014) - Hertweck, Benjamin; Zhang, Shiyu; Steigerwald, Thomas G.; Alt, Nicolas S. A.; Niewa, Rainer; Schluecker, Eberhard; Schlücker, Eberhard
Abstract The ammonoacidic crystal growth allows industrial production of bulk semiconductor materials like gallium nitride as a widely known material for applications in photonics. A limitation of this process is strong corrosion of the growth autoclave which consequently leads to high impurity density in grown crystals, even if the autoclave is partly lined with state‐of‐the‐art systems. Innovative metallic liner technologies are evaluated which allow a complete lining of the autoclave and peripheral parts. In this way, bridging the gap between fundamental research regarding the corrosive degeneration of possible liner materials and the implementation of novel lined autoclaves for improved growth conditions. Screening tests to find suitable materials and evaluate its potential for development of a liner technology are described.